Natural history and risk factors of IgE-mediated cow's milk protein allergy in infants - Shao, M J (Zhonghua er ke za zhi = Chinese journal of pediatrics, 2023)
Objective: To investigate the natural history and risk factors for continued allergy in infants with IgE-mediated cow's milk protein allergy (CMPA). Methods: This was a prospective cohort study that included 72 infants under 24 months of age diagnosed with IgE-mediated CMPA in the allergy clinic of the Children's Hospital, Capital Institute of Pediatrics from October 2019 to November 2020. General information, clinical manifestations, serum total IgE, cow's milk specific IgE, and cow's milk protein component specific IgE were collected. Follow-ups were conducted at 24 and 36 months of age, and the patients were divided into the persistent allergy group and the tolerance group based on whether they developed cow's milk tolerance at 36 months of age. Mann-Whitney U test, chi-square test, and binary Logistic regression were used for intergroup comparison and multivariate analysis. Results: Among the 72 CMPA children, there were 42 boys and 30 girls, with an age of 10 (7, 15) months at enrollment. Cow's milk protein tolerance was observed in 32 cases (44%) and 46 cases (64%) at 24 and 36 months of age, respectively. There were 26 cases in the persistent allergy group and 46 cases in the tolerance group. The proportion of respiratory symptoms, history of wheezing, positive specific IgE for α-lactalbumin and the total IgE level in the persistent allergy group were higher than that in the tolerance group (7 cases (27%) vs. 0, 6 cases (23%) vs. 2 cases (4%), 67% (14/21) vs. 26% (10/39), 225 (151, 616) vs. 48 (21, 185) kU/L, χ2=10.82, 4.16, 9.57, Z=4.07, all P<0.05). Multivariate Logistic regression analysis showed that anaphylaxis (OR=21.14, 95%CI 2.55-175.14, P=0.005), a history of allergic rhinitis (OR=5.94, 95%CI 1.54-22.86, P=0.005), elevated milk specific IgE (OR=1.04, 95%CI 1.01-1.08, P=0.024), and positive casein specific IgE (OR=6.64, 95%CI 1.39-31.69, P=0.018) were risk factors for continuous CMPA. Conclusions: Most infants with IgE-mediated CMPA can achieve tolerance within 3 years. Anaphylaxis, a history of allergic rhinitis, elevated milk specific IgE levels, and casein sensitization are risk factors for continuous allergy